A novel Huntington's disease mouse model to assess the role of neuroinflammation on disease progression and to develop human cell therapies. (12th March 2021) - Dahlenburg, Heather; Cameron, David; Yang, Sheng; Bachman, Angelica; Pollock, Kari; Cary, Whitney; Pham, Missy; Hendrix, Kyle; White, Jeannine; Nelson, Haley; Deng, Peter; Anderson, Joseph S.; et al.
Abstract: Huntington's disease (HD) is a fatal autosomal‐dominant neurodegenerative disease caused by a trinucleotide CAG repeat expansion of the huntingtin gene ( HTT ) that affects 1 in every 10 000 individuals in the United States. Our lab developed a novel immune deficient HD mouse strain, the YACNSG, from a commonly used line, the YAC128 mouse, to enable transplantation studies using engineered human cells in addition to studying the impact of the immune system on disease progression. The primary goal of this project was to characterize this novel immune deQficient HD mouse model, using behavioral assays and histology to compare this new model to the immune competent YAC128 and immune deficient mice that had engraftment of a human immune system. Flow cytometry was used to confirm that the YACNSG strain lacked immune cells, and in vivo imaging was used to assess human mesenchymal stem/stromal cell (MSC) retention compared with a commonly used immune deficient line, the NSG mouse. We found that YACNSG were able to retain human MSCs longer than the immune competent YAC128 mice. We performed behavioral assessments starting at 4 months of age and continued testing monthly until 12 months on the accelerod and in the open field. At 12 months, brains were isolated and evaluated using immunohistochemistry for striatal volume. Results from these studies suggest that the novel immune deficient YACNSG strain of mice could provide a good model for human stem‐cell based therapies and that the immune system appears to play an important role in the pathology of HD. Abstract : To create the novel HD strain, the YAC128 was backcrossed with NSG mice to produce an immune deficient HD mouse model.